ANALYSIS OF FINANCIAL PERFORMANCE OF PT. TELEKOMUNIKASI INDONESIA TBK 2017-2019 - Behuku, Dean Russel Jonathan; Wahda; Taba, Muhammad Idrus (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The study aimed to assess the financial performance of PT. Telekomunikasi Indonesia Tbk for the 2017-2019 period based on the Decree of the Minister of State-Owned Enterprises Number: KEP-100/MBU/2002.The data collection technique used was documentation, analyzing financial reports for the specified period. The results indicated that in 2017, the company's financial performance was categorized as "unwell" with a rating of BBB. In 2018, it was also classified as "unwell" with a rating of BB. In 2019, PT Telekomunikasi Indonesia Tbk was predicted to be in the "unwell" category with a rating of BBB. These assessments were based on predetermined indicators outlined in the aforementioned decree. The findings aim to provide valuable insights and information for the company to enhance its financial performance in the future.